Fluctuation aftereffect in magnetic materials - Street, R.; Crew, D.C. (IEEE transactions on magnetics, 1999)
Time dependence of magnetization under constant field conditions is exhibited by all materials subject to hysteresis. The phenomenon is a consequence of thermal activation of irreversible magnetization effects from metastable to stable states. Experimental observations of time dependence may be accounted for by considering distributions of the energy required for activation of the metastable states. Two simple cases are considered in this paper. The first involves a fixed value activation energy distribution; the second is concerned with magnetization events that all have the same value of activation energy. The latter is applicable to describing magnetization of magnetooptic films. It is shown that the results of measurements of time dependence of magnetization over wide ranges of time and field are useful in distinguishing between different mechanisms involved in magnetization reversal processes.